Wear behavior of in situ polymerized carbon nanotube/ultra high molecular weight polyethylene composites - Park, Hong-Jo; Kim, Jihun; Seo, Yongsok; Shim, Junho; Sung, Moon-Yong; Kwak, Soonjong (SPRINGER, 2013)
A carbon nanotube (CNT)/ultra high molecular weight polyethylene (UHMWPE) composite has been prepared through in situ polymerization of ethylene using Ti-based Ziegler-Natta catalysts fixed on the surface of CNT. The in situ polymerization of ethylene produced CNTs regularly encapsulated with UHMWPE, which showed very uniform dispersion of CNTs in the UHMWPE matrix after direct molding. In tensile and ring-on-block wear tests, the in situ polymerized composites showed mechanical and wear properties superior to mechanically blended composites. In particular, the polymerized composite displayed a remarkable suppression of abrasive wear, which was the wear mechanism observed in unfilled UHMWPE and mechanically blended composites; the in situ polymerized composite containing about 10 wt% of CNT had an approximately 2.5 times lower wear rate than unfilled UHMWPE. Moreover, the polymerized composite showed higher thermal conductivity with CNT content when compared to the blended composites, which suggests an easier transfer of heat generated during a severe wear operation.
Keywords: ZIEGLER-NATTA POLYMERIZATION; SURFACE CHARACTERIZATIONS; THERMAL-CONDUCTIVITY; RAMAN-SPECTROSCOPY; CHEMISTRY